Fostering an Innovative Work Culture in Indonesian Retail: Inclusive Leadership and Perceived Organizational Support Through Work Engagement - Purwasih, Dwi Cynthia; Pareke, Fahrudin JS (Jurnal Aplikasi Manajemen, 2025)
In the context of accelerated transformation and intense competition, organizations increasingly rely on employee innovation to ensure their continued success. Therefore, it is important to understand the factors that can drive innovative work behavior in the workplace. This study aims to investigate the effect of inclusive leadership and perceived organizational support on innovative work behavior, with work engagement as a mediating variable. This study uses a quantitative approach with a survey method in the form of a structured questionnaire. The population in this study was all Indomaret employees in Bengkulu City, with a non-probability sampling technique. A total of 210 respondents participated by completing a structured questionnaire. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method through SmartPLS software version 4. The findings indicate that inclusive leadership and perceived organizational support have a substantial impact on work engagement. Furthermore, both factors have been shown to directly and positively influence employee innovative work behavior. Furthermore, this study found that work engagement mediates this relationship, with a more pronounced mediation effect observed between perceived support and innovation than between inclusive leadership and innovation. Testing the mediation model of work engagement in the context of modern retail in Indonesia is still rarely studied, especially with a focus on inclusive leadership and POS simultaneously. The main theoretical contribution of this study is to confirm that work engagement serves as an important mechanism that transforms a supportive organizational environment into innovative behavior by increasing employees' energy, dedication, and intrinsic motivation. The practical implications of this phenomenon encourage organizations to cultivate inclusive leadership and a supportive environment to encourage employee innovative behavior.